Generalized Seizure Due To Acute Hyperosmolar Hyponatremıa Followıng Coronary Angıography: A Lesson Learned From A Case Report - Mehmet Coᶊgun; Yilmaz Gunes; Isa Sincer; Aslı Mansiroglu; Oğuz Kayabaᶊi (Faculty of Medicine Universitas Padjadjaran, 2019)
Hyponatremia is a common electrolyte disorder, but symptomatic hyponatremia following coronary angiography is rare. Although patients with hyponatremia are generally asymptomatic, neurological manifestations may result in lethal complications.Here we presented a 69-year-old female, admitted for elective coronary angiography due to exertional chest pain. Seven hours later after coronary angiography, however, the patient had a headache, temporary mental confusion and her speech was slurring. A brain magnetic resonance imaging (MRI) test, arterial blood gas analysis, and the neurological examination were carried out. The neurological examination showed no focality and brain diffusion MRI was normal. Arterial blood gas analysis revealed sodium of 110 mmol/L and potassium of2.8 mmol/L. The patient was treated with hypertonic saline (3% NaCl) and vasopressin antagonist tolvaptan 15 mg at first and isotonic saline (0,09 NaCl) with a gradual normalization of electrolytes. Diagnosis of acute hyperosmolar hyponatremia should be considered in patients with developing mental or behavioral abnormalities following coronary angiography.